Fabrication of antimony doped tin disulfide thin films by an inexpensive, modified spray pyrolysis technique using nebulizer. (August 2018) - Anitha, N.; Anitha, M.; Saravanakumar, K.; Valanarasu, S.; Amalraj, L.
Abstract: The SnS2 and antimony (Sb) doped SnS2 thin films were effectively synthesized on glass substrates for different antimony doping concentrations (2, 4, 6, 8 at. %) using nebulized spray pyrolysis technique. The XRD analysis showed that all the films are polycrystalline having hexagonal structure with (001) preferential orientation. It was seen from the SEM photographs that the doping causes remarkable changes in the surface morphology. EDAX analysis clearly confirms presence of expected elements tin, sulfur and antimony in the final product, in appropriate proportions. Optical study exhibits that the band gap value of SnS2 film decreases gradually with the increase in Sb doping concentration, reaching minimum band gap value of 2.55 eV at 6 at.% and starts increasing thereafter. Photoluminescence spectra depicted that the intensity of the emission peaks significantly varied with doping concentrations. The electrical study shows that the minimum resistivity value of 11 Ω cm with notable higher values of carrier concentration and mobility is achieved for 6 at.% of SnS2 : Sb film. The Raman spectra exposed that SnS2 films had a broad peak at 314 cm −1 . Highlights: Highly textured (001) oriented un-doped and Sb doped SnS2 thin films were prepared by nebulized spray pyrolysis technique. Band gap of SnS2 thin films was tuned by doping with antimony. The direct band gap energy was about 2.55 eV, suggesting the potential use of SnS2 in thin film solar cells. Conductivity of SnS2 thin films increases with increased amount of Sb.